UNIVERSAL EXERCISE UNIT THERAPY HAS EFFECTS ON SOCIAL AND MOTOR FUNCTION OF 8 YEARS OLD HYPERACTIVE BOY WITH AUTISM SPECTRUM DISORDER - Farjad Afzal; Sidra Manzoor (Journal of University Medical & Dental College, 2017)
ABSTRACT: A 08 years old child; know case of autism with hyperactive sub with impairments in behavioral, social and motor function was selected for therapy in universal exercise unit along with social skills training, attending skills training, self help skills training and adaptive sports activities. Pediatric evaluation of disability inventory (PEDI) was used to measure sensory functions, motor function and social function and then compared the pre-treatment and post-treatment measurements. Pre-treatment self care, mobility and social function score were 49, 40 and 45 and post treatment score were 58, 50, and 57 respectively on pediatric evaluation disability inventory scale. Result of this study showed that universal exercise combine with social skills training, attending skills training, self help skills training and adaptive sports activities can change the motor function, self help function and social function of a child with autism.